Safety Behavior among Workers of Rubberwood Factory in Nakhon Si Thammarat Province - หัตถประดิษฐ์, ฟารอน; บุญละออ, โสภา; อมประนาม, ขนิษฐา (Journal of Health Science of Thailand, 2022)
This cross-sectional research aimed to study safety behavior at work among workers in a rubberwood factory, Nakhon Si Thammasat Province. The study samples were 344 workers in the factory who were selected by simple sampling technique. Data collection was conducted by using a set of questionnaire during July – December 2019; and the data were analyzed with descriptive statistics and presented by percentage and standard deviation, and multiple regression analysis. The results revealed that the majority of workers were female (66.3%), aged between 36-45 years old (35.3%), their duties were laying out planks (25.4%), with working history of 2-5 years (52.6%). Their safety behaviors were at high level (96.5%). The factors affecting safety behaviors among workers with statistical significance (p<0.05) were age, perceived severity, and attitude. This study recommended that factories should focus on providing safety training for young and new workers, determine safety precautions, and create a positive attitude toward the working process. The rubberwood factories should have proactive health care plans for occupational health workers as well.